Lock-in effects in competitive bidding schemes for payments for ecosystem services: Revisiting the fundamental transformation - Nora Vogt; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
Competitive bidding is considered to be a cost-effective allocation mechanism for payments for ecosystem services. This article shows that competition is not a necessary condition for sustaining cost-effectiveness in the long run. In a repeated conservation auction, learning, specific investments and the creation of social capital bias the chances of winning a follow-up contract in favour of former auction winners. Applying the concept of fundamental transformation (Williamson 1985), we argue that this asymmetry weakens competition and leads to lock-in effects between the auctioning agency and a stable pool of sellers with uncertain consequences for cost-effectiveness. We compare data from two laboratory experiments on auction-based conservation programmes and show under which conditions lock-in effects are likely to occur in a controlled environment. Our findings demonstrate lock-in effects do not erode the effectiveness of an auction but change the rules of the game towards more favourable conditions for the provision of the targeted good or service. In view of the empirical evidence for a superior performance of long-term contract relationships compared to low-cost short-term contracting, we discuss directions for follow-up empirical work.
Keywords: 330; trust; social capital; asset specificity; cost-effectiveness; conservation auctions; payments for ecosystem services